THE IMPACT OF ENGLISH ON INTERNATIONAL COLLABORATION IN TECHNICAL FIELDS - SOLIEV MIRZOKHID MUSOEVICH, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract In the era of globalization, international collaboration has become a fundamental characteristic  of  technical  and  scientific  development.  Engineers,  researchers,  and technical  specialists  increasingly  cooperate  across  national  borders  to  implement complex  projects,  exchange  knowledge,  and  promote  innovation.  In  this  global environment, English has emerged as the dominant language of communication. The widespread  use  of  English  in  scientific  publications,  international  standards, multinational corporations, and digital platforms has significantly shaped the structure and efficiency of technical cooperation. This article examines the impact of English on international collaboration in technical  fields.  It  explores  the  role  of  English  as  a  lingua  franca  in  research dissemination, multinational engineering projects, professional mobility, and global standardization. The paper also considers challenges related to linguistic inequality and the importance of English education in technical institutions. The study concludes that English functions as a strategic tool that enhances coordination, accelerates innovation, and strengthens international integration in technical disciplines.